Adsorption and regeneration method for deteriorated plant transformer oil - XIAO YAPING; XIAO SA; ZHANG ZHIYU; WANG LIJUN; REN QIAOLIN; DENG HUA; HUANG DANLI; JIANG TAO; LIU XIAORAN; XIE JINGLONG; LIU HUI; LU MANG (2017)
The invention relates to a method for collecting and recycling waste insulating oil of a transformer, and is mainly used for recovery and recycling of the waste transformer oil. The method comprises the following steps: a transformer oil recovery and processing center is established to recycle the waste oil; new oil drums and waste oil drums in a transformer substation are subjected to oil level monitoring and GPRS positioning; an oil level is monitored through a liquid level sensor, data of the oil level is transmitted to a data processing module through a wireless data acquisition module, and the data processing module transmits the data to a background server through a 4G communication module; GPRS positioning modules are installed on the new oil drums and the waste oil drums in the transformer substation; and after the oil level monitored through the liquid level sensor reaches an alarm value, an alarm station is clicked to generate a navigation path, a voice prompt is given out in the course of the proce